KOMPETENSI PELAJAR MEMBINA PENGATURCARAAN KAWALAN LOGIK (PLC) BAGI KURSUS AUTOMASI INDUSTRI DI KOLEJ VOKASIONAL - Ab Rahman, Azmanirah; Zolkifly, Nur Anati; Muhamad Hanafi, Nurfirdawati; Mohamad Yusof, Anizam (Online Journal for TVET Practitioners, 2018)
Programmable Logic Controller (PLC) is widely used in manufacturing industry nowadays. Hence, the competence of students towards PLCs is important to produce graduates who can meet the demands of the industry. In this regard, this study was conducted to identify the level of competency students in the Electronic Technology programme at Vocational College (VC) in terms of cognitive and psychomotor aspects in developing PLC programming. The design of the study is by survey. This study was conducted in three KVs in Perak and Johor. A total of 90 respondents were involved in this study. The research instrument used was test questions to measure knowledge level while practical question is used for measuring student skills. The findings were analyzed by using descriptive statistics and presented in percentages. Based on the findings of the study, the students competent at both level. However, overall students tend to master the theory rather than practice. Therefore, the findings from this study can be used by KV lecturers for Industrial Automation courses in order to improve the quality of teaching and learning.